2017
DOI: 10.1017/s0022149x17000074
|View full text |Cite
|
Sign up to set email alerts
|

Copro-PCR prevalence of Echinococcus granulosus infection in dogs in Kerman, south-eastern Iran

Abstract: The main objective of this study was to determine the prevalence of taeniid parasites and the specific detection of Echinococcus granulosus using copro-DNA polymerase chain reaction (PCR) analysis in the stray dogs of Kerman, south-eastern Iran. From September 2013 to May 2014, faecal samples of stray dogs were collected from different parts of the city of Kerman and its suburbs. Faecal samples from dogs were collected randomly within 24 h of defecation. All samples were transferred to the research lab and cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…It has been reported that there is no cross-amplification with Taenia hydatigena , T. ovis , Dipylidium caninum , or E. multilocularis (1). In previous studies from around the world, the prevalence of E. granulosus was found to be between 3.6% and 25.9% by molecular biological techniques (21). The present study using the copro-PCR technique revealed that E. granulosus infection is present in 4% of dog faecal samples in Van Province.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…It has been reported that there is no cross-amplification with Taenia hydatigena , T. ovis , Dipylidium caninum , or E. multilocularis (1). In previous studies from around the world, the prevalence of E. granulosus was found to be between 3.6% and 25.9% by molecular biological techniques (21). The present study using the copro-PCR technique revealed that E. granulosus infection is present in 4% of dog faecal samples in Van Province.…”
Section: Discussionmentioning
confidence: 96%
“…The present study using the copro-PCR technique revealed that E. granulosus infection is present in 4% of dog faecal samples in Van Province. Although extensive studies have been carried out in the world on the determination of the species of canine echinococcosis at the molecular level (3, 9, 21, 22), few researchers have used the copro-PCR test in Turkey.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cystic echinococcosis (CE), a major zoonotic helminth infection, imposes a socioeconomic burden in many countries all over the world, including Iran [1][2][3][4][5]. The metacestode of Echinococcus granulosus harbors in the viscera of wide variety of herbivores, including sheep, goats, cattle, and camel.…”
Section: Introductionmentioning
confidence: 99%
“…Dogs have been found frequently infected with these tapeworm species. For E. granulosus , the prevalence ranges from 3.6% to 25.9% in Asia, Europe and Africa using molecular tools 4 . It has been shown that T. hydatigena is one of the most prevalent Taenia species in dogs and sheep in Iran, reported in 28.5-53.0% of dogs, 9.1% of foxes, 10% of jackals and 12.8% of sheep in different parts of the country 5 - 7 .…”
Section: Introductionmentioning
confidence: 99%